EMPATHY OF THE BANCASSURANCE CHANNEL: AN EMPIRICAL STUDY - Choudhury, Mousumi; Singh, Ranjit; Kajol, K.; Rai, Shashi Kant (Indian Journal of Finance and Banking, 2020)
Purpose: The purpose of the study is to assess the customers’ perception regarding empathy exhibited by the bancassurance channel and factors affecting it.Design/Methodology/Approach: Using random sampling, the data was collected from customers of several branches of State bank of India in Guwahati city of Assam, who have availed life insurance services from these branches. Tool of structured questionnaire was used to collect primary data. Mean, standard deviation, regression analysis was used to analyze the data and draw logical conclusions. Findings: The study shows that customer perceives bancassurance channel to have a high level of empathy towards customers. It was also found that none of the demographic variables considered in the study have any impact on influencing perception. Therefore, policymaker can adopt one fits all approach in the case of demographic aspects to improve the empathetic nature showed by the bancassurance channel.Research Limitations: The study takes into consideration the customers who have bought Life insurance service from various branches of State Bank of India, Guwahati, Assam, India.Originality: The study is first of its kind in assessing customer’s perception of empathy shown by the bancassurance channel. The study will be useful for researchers, academicians and those working in the area of bancassurance and in their understanding about factors influencing customer experience, satisfaction and retention strategy.Major Conclusion: The study finds that customers of the bancassurance channel perceive that the channel demonstrates high empathy. Therefore, policymaker can advocate for an increase in penetration of life insurance through the bancassurance channel. As there is no association between the demographic factors and customers’ perception towards empathy shown by the bancassurance channel, policymaker can adopt one fits all approach in the case of demographic aspects to improve the empathetic nature showed by the bancassurance channel.